Legal Position of Marriage Agreement Deeds that are Not Registered in Court (Study of Supreme Court Decision Number 598 PK/PDT/2016 dated November 24, 2016) - Kurnia Illahi, Ariyani (TABELLIUS: Journal of Law, 2025)
A prenuptial agreement is an important legal instrument in regulating marital property as regulated in Article 29 of Law Number 1 of 1974 concerning Marriage. Registration of a prenuptial agreement in a court or authorized institution is a formal requirement that determines the legal force of the agreement, particularly in providing legal certainty for the parties and protection for third parties. However, in practice, prenuptial agreements are still found to be made before a notary but not properly registered, giving rise to legal uncertainty regarding their validity and legal consequences. Supreme Court Decision Number 598 PK/PDT/2016 is an important precedent that provides a new perspective in understanding the legal status of unregistered prenuptial agreements. This study aims to analyze the legal status of unregistered prenuptial agreements in court and the legal implications they have for the parties and third parties. The normative juridical method with a statutory and conceptual approach, analyzes Supreme Court Decision Number 598 PK/PDT/2016 as a case study. The results of the study indicate that unregistered prenuptial agreements remain binding on the parties based on the principle of pacta sunt servanda (Article 1338 of the Civil Code), but do not have legal force against third parties according to the principle of publicity. The legal implications include difficulties in proving the agreement in court, the application of a unity of property regime to third parties, the risk of execution of assets by creditors, and complexity in inheritance distribution. The study recommends the need for regulatory revisions, simplification of registration procedures, implementation of electronic systems, and increased public outreach to ensure legal certainty and protection of the rights of all parties.